Simultaneous intrathecal injection of muscimol and endomorphin‐1 alleviates neuropathic pain in rat model of spinal cord injury. Issue 5 (18th March 2020) - Hosseini, Marjan; Karami, Zohreh; Yousefifard, Mahmood; Janzadeh, Atousa; Zamani, Elham; Nasirinezhad, Farinaz
Abstract: Introduction: Due to side effects of medications used for chronic pain, combination therapy seems to be an appropriate solution for alleviation of chronic pain and reducing the side effects. The role of inhibitory GABA system is well proven in reducing neuropathic pain. Also, special attention has been focused on endogenous morphine (endomorphins) in reducing chronic pain originates from damage to the nervous system. The purpose of this study is to investigate the analgesic effect of simultaneous administration of GABA agonist and endomorphin‐1 on neuropathic pain in rat model of spinal cord injury (SCI). The role of oxidative stress, NR1 subunits of NMDA receptors, and α2 subunits of GABA receptors in the spinal cord has also been investigated. Methods: Spinal cord at level of T6–T8 was compressed. Three weeks after spinal cord injury, muscimol and endomorphin‐1 were injected (intrathecally once a day for 7 days) individually or in combination. Mechanical and cold allodynia, thermal and mechanical hyperalgesia were evaluated before injection and 15 and 60 min after injection. At the end of behavioral experiments, histological and biochemical evaluations were done on prepared spinal cord samples. Results: Isobologram results showed that combination therapy significantly increased the pain threshold comparing to injection of endomorphin‐1 (EM) or muscimol alone. Histological studies indicated the increased expression of α2 subunits of GABA receptors, and NR1 subunits of NMDA receptors in the spinal cord. The combination therapy also increased the glutathione (GSH) and superoxide dismutase (SOD) level and decreased the malondialdehyde (MDA) levels in the spinal cord. Conclusion: Simultaneous administration of muscimol and endomorphine‐1 could be a new candidate for alleviation of pain resulting from spinal cord injury. Abstract : Simultaneous intrathecal administration of muscimol and endomorphin‐1 as a new candidate for the alleviation of pain resulting from SCI.